2007
DOI: 10.1254/jphs.fp0070314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serotonergic Anxiolytics on the Freezing Behavior in the Elevated Open-Platform Test in Mice

Abstract: Abstract. Freezing behavior is thought to be a sign of fear in animals. We examined whether the freezing behavior during the elevated open-platform stress, which is a psychological stressor without painful stimulus, is modulated by serotonergic neurotransmission and would be a useful marker for screening anxiolytic and / or antidepressant. Male ICR mice (6 -8-week-old) were individually placed on an elevated open-platform and the duration of freezing behavior of mouse was measured for 10 min. Fluoxetine and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
2
22
0
1
Order By: Relevance
“…These results suggest that, in addition to the 5-HT systems, the DA and NA systems might participate in the anxiolytic-like effects of chlorpheniramine. Recently, we indicate that a treatment with 5-HT synthesis inhibitor, pCPA, increased the duration of freezing in mice subjected to the elevated open-platform test (Miyata et al 2007a). In that report, we also indicated that the selective NA uptake inhibitor, reboxetine, and the non-selective 5-HT/NA uptake inhibitors tricyclic antidepressants, imipramine and clomipramine, did not affect the duration of freezing.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…These results suggest that, in addition to the 5-HT systems, the DA and NA systems might participate in the anxiolytic-like effects of chlorpheniramine. Recently, we indicate that a treatment with 5-HT synthesis inhibitor, pCPA, increased the duration of freezing in mice subjected to the elevated open-platform test (Miyata et al 2007a). In that report, we also indicated that the selective NA uptake inhibitor, reboxetine, and the non-selective 5-HT/NA uptake inhibitors tricyclic antidepressants, imipramine and clomipramine, did not affect the duration of freezing.…”
Section: Discussionmentioning
confidence: 80%
“…To evaluate the anxiolytic-like effects of chlorpheniramine, we used two different behavioral tests. The conditioned fear test detects the punishment-evoked anxiety of animals, which is sensitive, particularly to serotonergic anxiolytics (Tye et al 1977), and the elevated open-platform test that could predict anxiolytic-like effects (Miyata et al 2007a). The fact that chlorpheniramine reduced freezing in both tests might indicate that this antihistamine drug exerts anxiolytic-like effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations